Green-chemistry of by-products from Sai-Nam-Phueng orange in Thailand (1): Recovering a valuable source of bioactive compounds using response surface methodology, antioxidant, and cytotoxicity - Kanchanok Kodchakorn; Prachya Kongtawelert (Waste Management Bulletin)
Citrus reticulata Blanco, specifically Sai-Nam-Phueng orange traditionally considered by-products, are rich in phytochemicals — limonoids, flavonoids. This study compared seeds and peels for the phytochemical content and antioxidant activity. Using single-factor experiments and response surface methodology (RSM), the effects of ethanol concentration, solvent-to-solid ratio, and temperature on extract yield were optimized. The study found optimal conditions to be 70.50 % ethanol, 28.11 mL/g solvent-to-solid ratio, and 69.99 °C. Experimental values are in reasonable agreement with predicted values. Phytochemical contents were characterized using HPLC, mass spectrometry, and NMR spectroscopy, successfully demonstrating efficient of purified compounds from orange by-products and cost-effective extraction methods.Kewords: Antioxidant, Green-extractions, Phytochemicals, Response Surface Methodology, Cytotoxicity.